Rola interleukiny 17 w chorobach układu oddechowego u dzieci - Kleszyk, Magdalena; Machura, Edyta; Jaszczura, Majka; Ziora, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Chronic or recurrent symptoms of respiratory diseases are the most common cause of visits to the pediatrician and hospitalization of children. Several studies in adults and children have shown that the profile of cytokines, including interleukin-17 (IL-17) in body fluids, is associated with the etiology of the symptoms of bronchopulmonary diseases. Synthesis of IL-17 strongly stimulates inflammation, autoimmune diseases, and respond to infections (viruses, bacteria, and fungi) and it is also involved in allergic reactions (asthma and allergic rhinitis). The production of IL-17 in the airway is stimulated by virus products and bacterial polypeptides, leading to an influx of neutrophils and release by a number of substances (such as metalloproteinases, elastase, or free radicals), and this may have an adverse effect on the pathomechanism of chronic lung diseases including asthma or cystic fibrosis. IL-17 is associated with airway hyperresponsiveness – existing studies indicate a compound Th2 responses and eosinophilia with Th17 response and neutrophilia. The article discusses the possible role of IL-17 in the development of chronic or recurrent symptoms of respiratory diseases in children